Impact properties of polymers - Sim, J.K.F (Universiti Malaysia Sarawak, UNIMAS, 2009)
Polymer is made up from many chemically bonded parts or monomers that themselves are bonded together to form a solid. Polymeric materials such as PVC, nylon and nylatron are used as the specimen for this testing. In this study, the drop weight testing had been conducted to the specimens under the impact loading using accelerometer. The drop weight was dropped on the specimen from the different heights. The accelerometer is functioning as a sensor to produce a voltage output which is proportional to the acceleration of the drop weight where the accelerometer is mounted on it. The data acquired from the accelerometer was then converted to acceleration, velocity and displacement. The stress-strain curves were plotted in the further steps. The results show that the voltage produced by the accelerometer is influenced by the height of the drop weight from the specimen. At higher height, more impact energy is available for the drop weight to knock the specimen. The results of the drop weight testing also indicate that the value of modulus of elasticity is increasing from nylon → PVC → nylatron at the same strain rate. This shows that the nylatron has the highest strength among these materials.